Martyr Devotion in the Alexandrian School: Origen to Athanasius - McGuckin, John Anthony (Studies in church history, 1993)
The Christian interpretation of fatal persecution was a complex one with distinct ecclesial themes merging with Jewish elements from apocalyptic and biblical literature, as well as Hellenistic motifs such as the constancy of the Socratic martyr. The New Testament understanding of the term ‘martyr’ is predominantly that of legal witness, although some specific senses of blood-witness are emerging already in the first century and have become common by the second. Varying reactions can be traced in the literature of different parts of the Church: for example, in Rome, Alexandria, Asia, Africa, or Palestine. This paper looks primarily at the Egyptian interpretation as a microcosm of the general development of the role of martyrs, and does so by reference to the writings of the theologians whose works cover the main phases of that process. It highlights the distinction that existed between the sophisticated literary interpretation of martyrdom, and the forms of popular devotion that flourished among the non-literate peasantry. The tension between the two approaches, witnessed in both Origen and Athanasius, is demonstrably resolved by the time of Cyril, who represents the harmonious synthesis of both traditions in the new conditions of Christian political ascendancy in fifth-century Byzantine Egypt. The peculiar circumstances of the Egyptian Church, in particular the unusually radical separation that existed there between town and country (and the class and cultural divisions reflected in that), as well as the specific challenge posed to Christianity by the enduring vitality of the old Egyptian religions in the countryside, both left their marks on the specific form of martyr devotion in Christian Egypt, but the most noteworthy aspect is arguably the subtext of the theological encomia of martyrdom that seems to have the definite concern of subjugating the popular devotion to martyrs, confessors, and ascetics to the interests of the Church hierarchies.